2016
DOI: 10.1128/jvi.02139-15
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Rebound Plasma HIV Includes Cells with Identical Proviruses That Are Transcriptionally Active before Stopping of Antiretroviral Therapy

Abstract: Understanding the origin of HIV variants during viral rebound may provide insight into the composition of the HIV reservoir and has implications for the design of curative interventions. HIV single-genome sequences were obtained from 10 AIDS Clinical Trials Group participants who underwent analytic antiretroviral therapy (ART) interruption (ATI). Rebounding variants were compared with those in pre-ART plasma in all 10 participants and with on-ART peripheral blood mononuclear cell (PBMC)-associated DNA and RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
135
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 31 publications
24
135
1
Order By: Relevance
“…However, there is minimal evidence for transcription of defective proviruses (14,27). Here, we were able to identify the presence of clonally expanded defective provirus populations and to demonstrate ongoing transcription of these expanded "defective" proviral clones in two different patients (Pts 5 and 7) with pVL < 40 copies per milliliter (clones ii and vi in Fig.…”
Section: Significancementioning
confidence: 62%
“…However, there is minimal evidence for transcription of defective proviruses (14,27). Here, we were able to identify the presence of clonally expanded defective provirus populations and to demonstrate ongoing transcription of these expanded "defective" proviral clones in two different patients (Pts 5 and 7) with pVL < 40 copies per milliliter (clones ii and vi in Fig.…”
Section: Significancementioning
confidence: 62%
“…To look for evidence of ongoing viral replication during ART, HIV populations in samples taken at baseline were compared with the populations present after long-term ART. Three measures of evolution were assessed for significant change over time: (a) HIV-1 genetic diversity, measured as the average pairwise distance (APD), from early infection to long-term infection; (b) genetic divergence from the founder virus(es) using a test for panmixia (3,12,26,27); and (c) root-to-tip distances in maximum-likelihood (ML) trees (3,12,27). ML trees were rooted in 2 ways: first, on an outgroup (HIV subtype C consensus; www.hiv.lanl.gov), and second, on the majority sequence of the baseline sample (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, expanded clones harboring replication-competent proviruses were identified by sequence matches between viruses recovered in multiple different viral outgrowth cultures, revealing that most of the HIV reservoir is maintained by cellular proliferation (4,5,41). Furthermore, proviruses with identical sequences, and thus likely to be in cell clones, were reported to be a source for rebound viremia after stopping ART (12). Collectively, these studies, along with the data shown here, demonstrate that proliferating, infected cells are a common mechanism of reservoir persistence that needs to be targeted to cure HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations